Pemberdayaan UMKM: Catatan Reflektif Hasil Meta Riset - Noor, Ida Ruwaida; Setyawati, Lugina (Masyarakat: Jurnal Sosiologi, 2010)
There are several aspects that can be seen in various studies to map the SMEs, that is the focus, methodology, conceptual basis, and the factors influencing it. Based on the focus, various studies SMEs been more centered on aspects of economic rather than socio-cultural. If any, shades of the economy remains strong. In terms of methodology, which is predominantly quantitative, although there are attempts to use qualitative methodology. Conceptually, the idea of the SMEs mostly placed within the framework of development rather than empowerment. In various studies it also appears that various factors affect the performance of SMEs, ranging from access to productive resources, low product specifications, production capacity is limited, and so forth.